Transcatheter versus surgical valve repair in patients with severe mitral regurgitation. (14th October 2021) - Koschutnik, M; Dannenberg, V; Dona, C; Nitsche, C; Kammerlander, A A; Mora, B; Bartunek, A; Wiedemann, D; Zimpfer, D; Huelsmann, M; Schneider, M; Bartko, P E; et al.
Abstract: Background: Transcatheter edge-to-edge mitral valve repair (TMVR) is increasingly performed, however, its efficacy in comparison with surgical MV treatment (SMV) is unknown. Methods: Consecutive patients with severe mitral regurgitation (MR) undergoing TMVR (68% functional, 32% degenerative) or SMV (9% functional, 91% degenerative; 23% MV replacement) were enrolled. To account for differences in baseline characteristics, propensity score-matching including age, EuroSCORE-II, left ventricular ejection fraction, and NT-proBNP was performed. A composite of heart failure (HF) hospitalization/death was defined as primary endpoint. Kaplan-Meier curves and Cox-regression analyses were used to investigate associations between baseline, imaging, and procedural parameters and outcome. Results: Between July 2017 and April 2020, 245 patients were enrolled, of which 102 patients could be adequately matched (73y/o, 61% females, EuroSCORE-II: 5.7%, p>0.05 for all). Despite matching, TMVR patients were sicker at baseline (higher rates of prior myocardial infarction, coronary revascularization, pacemakers/defibrillators, and diabetes mellitus, p<0.009 for all). Patients were followed for 28.3±27.2 months, during which 27 events (17 deaths, 10 HF hospitalizations) occurred.Postprocedural MR reduction (MR grade <2: TMVR vs. SMV: 88% vs. 94%, p=0.487) and freedom from HF hospitalization/death (log-rank: p=0.221) were similar at two years. By multivariable Cox analyses, EuroSCORE-II (adj.HR 1.07 [95% CI: 1.00–1.13], p=0.027) and postprocedural MR severity (adj.HR 1.85 [95% CI: 1.17–2.92], p=0.009) emerged as independent predictors of outcome. Conclusions: In this propensity matched, all-comers cohort, 2-year outcomes after TMVR versus SMV were similar. Given the reported favorable long-term durability of TMVR, the interventional approach emerges as valuable alternative for a substantial number of patients with functional and degenerative MR at high/prohibitive surgical risk. Funding Acknowledgement: Type of funding sources: None.